Genitals evolve faster than other traits in Anolis lizards. (January 2015) - Klaczko, J.; Ingram, T.; Losos, J.
Abstract Male genitalia are thought to be particularly rapidly evolving morphological structures, but there have been few quantitative interspecific comparisons between the evolutionary rates of genital and nongenital traits. We characterize the morphology of hemipenes in 25 Caribbean Anolis lizard species, and compare rates of hemipenial evolution to those of traits related to ecology or visual signaling. Using phylogenetically based comparisons of rates of evolutionary divergence, we show that genital traits evolve more rapidly than nongenital traits in anoles.